EFFECT OF TRAINING SCREEN TIME ON THE QUALITY OF PARENT-CHILD INTERACTION - Shelin Apriliana Putri (JIV-Jurnal Ilmiah Visi, 2022)
Many previous studies have shown the relationship between excessive screen time duration and child-parent interactions. Unfortunately, there are still few studies that evaluate interventions to increase child-parent interaction for children with the management of children's screen time duration. This study aims to examine the effect of screen time training on improving the quality of interaction between children and parents. Measuring the level of interaction between children and parents using a questionnaire given to parents before and after the training was held. Participants involved in this study were children aged 0-5 years (N = 21) who were taken randomly from all children aged 0-5 years in Suronalan Village. The data obtained were analyzed using the Wilcoxon sign rank test. The results showed that there was a significant difference between the results of the pre-test and post-test data. The conclusion from this research is that screen time training can improve the quality of interaction between children and parents.